Consumer intent to disclose personal information in ecommerce: a comparison of Estonia and the United States - Robinson, Stephen Cory, author; Hallahan, Kirk, advisor; Rouner, Donna, committee member; Plaisance, Patrick, committee member; Walrave, Michel, committee member; Makela, Carole, committee member; Hyllegard, Karen, committee member (Colorado State University. Libraries, 2014)
An online survey conducted among participants in the US (n=248) and Estonia (n=225) examined willingness to disclose and perceived risks pertaining to disclosing personally identifying information (PII, also referred to as personal data in Europe) in ecommerce, as well as attitude toward disclosure in general, and anxiety disclosing personal data. Additionally, the study investigated how willingness to disclose and perceived risk of disclosing personal data were affected by demographic variables, trust in the Internet and trust in institutions, the Big Five personality dimensions found in the psychology literature (neuroticism, openness, agreeableness, conscientiousness, and extraversion), and four sets of perceived shopping benefits (opportunity benefits, bargain benefits, purchase benefits, and expected privacy benefits). Despite Estonia's advanced adoption and progressive policies and practices toward the Internet, Americans were more willing to disclose, exhibited more positive attitudes, demonstrated less anxiety, and were less concerned about perceived risks. For Estonians, ecommerce experience, perceived purchase benefits, and trust in the Internet and institutions were significant predictors of willingness to disclose personal data. Americans who perceived purchase benefits were found to be the most likely to disclose PII, while Americans with lower levels of education were also more willing to disclose. The study utilized a 17-item list of potential disclosure items (name, email address, etc.) and showed these can be categorized reliably into six sub-indices: contact information, payment information, life history information, financial/medical information, work-related information, and online account information. Further, a reliable efficient, 20-item scale was developed that can be deployed in future studies investigating the Big Five personality traits. Online disclosure consciousness (ODC) was introduced as a framework to conceptualize and empirically measure the gap between one's willingness to disclose and perceived risk pertaining to the overall 17-item index used in the study, the sub-indices, and particular items. Using 7-point Likert-type measures, the results showed significant gaps among participants both within and across nations. A 5-scenario online disclosure consciousness model is presented to explain the tradeoffs involved in making a disclosure decision, with absolute willingness to disclose and absolute perceived risk on the two extremes and theoretical midpoint where the two competing motivations cancel themselves out. Changes in a person's position along the continuum are posited to be influenced by marketers' initiatives, personal experiences, and external factors. Implications for theory, consumers, marketing practice, and public policy are discussed. The findings suggest that willingness to disclose and risk aversion can and should be analyzed empirically together. Thus, the ODC model provides an alternative conceptualization to the ideas of the privacy paradox, privacy calculus, and privacy cost-benefit ratios found in the literature. The study suggests consumers have a responsibility to educate themselves about online disclosure practices and how to protect their privacy. The findings also suggest marketers and policy makers should recognize that data disclosed online are not all equally sensitive to consumers. However, fostering trust, reducing risks, and promoting benefits are essential to the future of ecommerce.
Keywords: ecommerce; privacy; personally identifying information (PII); personal data; Estonia; disclosure